IRF7 is a Prognostic Biomarker and Associated with Immune Infiltration in Stomach Adenocarcinoma - Guo L; Fang T; Jiang Y; Liu D (International Journal of General Medicine, 2021)
Lili Guo,1 Te Fang,1 Yanhua Jiang,1 Dingsheng Liu2 1Department of Anesthesiology, First Affiliated Hospital, China Medical University, Shenyang, Liaoning, 110001, People’s Republic of China; 2Department of General Surgery, Shengjing Hospital of China Medical University, Shenyang, 110004, Liaoning, People’s Republic of ChinaCorrespondence: Dingsheng LiuDepartment of General Surgery, Shengjing Hospital, China Medical University, No. 36 Sanhao St, Heping District, Shenyang, 110004, Liaoning, People’s Republic of ChinaEmail Dingsheng-liu@hotmail.comBackground: Stomach adenocarcinoma (STAD) is one of the most prevalent malignances, ranking fifth in incidence and third in mortality among all malignances. Interferon regulatory factors (IRFs) play a vital role in immune response and tumor cellular biological process. The roles of IRFs in STAD are far from being systematically clarified.Methods: A series of bioinformatics tools, including GEPIA, UALCAN, TIMER, Kaplan–Meier plotter and LinkedOmics, were applied to explore the expression and clinical significance of IRFs in STAD.Results: IRF3/7 expression were upregulated in STAD in sub-group analyses based on race, gender, age, H. Pylori infection status, histological subtypes, tumor grade, individual cancer stages, and nodal metastasis status. High IRF3/7 expression were associated with poor overall survival (OS), post-progression survival (PFPS) and first progression (FP) in STAD. IRF3 and IRF7 were altered in 5% and 6% of all TCGA STAD patients. Further analysis revealed that IRF7 was significantly associated with the abundance of immune cells (B cells, Neutrophils and Dendritic cells) and the expression of most immune biomarkers. Enrichment analysis indicated that IRF7 was mainly involved in adaptive immune response, NOD-like receptor signaling pathway, Necroptosis, and Toll-like receptor signaling pathway. We also identified several IRF7-associated kinase and miRNA targets in STAD. The result of verified experiment revealed that ITF7 expression was increased in STAD tissues compared with normal tissues and prognosis analysis revealed that STAD patients with high IRF7 expression had a poor overall survival.Conclusion: IRF7 is upregulated in STAD and associated with poor OS, PPS and FP. Moreover, IRF7 is significantly associated with the abundance of immune cells and the expression of most immune biomarkers, suggesting that IRF7 is as a prognostic biomarker and associated with immune infiltration in STAD.Keywords: stomach adenocarcinoma, bioinformatics analysis, immune infiltration, IRF7